A randomised prospective comparative study of evaluation of dexmedetomidine an adjuvant to ropivacaine for ultrasound guided supraclavicular block - Murthy, V. S. S. N.; Hari Kiran Verma, N.; Acharya, Anand (International Journal of Clinical Trials, 2018)
Background: There are clinical evidences for efficacy of dexmedetomidine as an adjuvant to local anaesthetic for peripheral nerve block, but very few published study are available on continuation of dexmedetomidine, with ropivacaine for ultrasound guided supraclavicular block. The present study has been designed to elucidate the effect of dexmedetomidine, in combination ropivacaine on various parameters. Methods: During period of 2 year and 3 months 84 patients were enrolled for this study. Patient in Group A were received 15 ml of 0.5% ropivacaine with 100 microgram one ml dexmedetomidine and Group B were received 15ml of 0.5% of ropivacaine with 1 ml of normal saline. Drug solution was prepared by same individual and was not part of study. Results: Both the group were comparable to each other regarding demography profile. The duration of sensory block 644.96±72.4 min in group A and the duration of sensory block in Group B was 731.53±131.54 min with p value 0.00354. The duration of motor block was 661.5±29.25 in group A and 559.77±29.25 in Group B with P value 0.0001. Duration of analgesia in Group A was 457.06±34.47 min and it was 345.70±38.032 min in Group B. The supplementation of intravenous opioid was required in 3 patients in Group A and 10 patients in group B with P value 0.037. Conclusions: When 100 microgram of dexmedetomidine was added as an adjuvant to ropivacaine is associated with early onset of sensory and motor block, prolongation of sensory and motor block and duration of analgesia in comparison with ropivacaine alone.